Creative economy - Botirov Diyorbek Sohib’s Ogli; Usarbaev Ulugbek Alisher’s Ogli; Ismoilov Muhammad Omonboy’s Ogli; Davlataliyev Arslon Dilshod’s Ogli (Academia One Publishing, 2025)
This article explores the role of the creative economy in driving sustainable development, innovation, and cultural preservation on a global scale. The creative economy, encompassing industries such as art, design, media, and technology, fosters economic growth by leveraging creativity and knowledge. It plays a pivotal role in creating employment, promoting cultural identity, and enhancing social cohesion. However, challenges such as unequal access to resources, intellectual property concerns, and the digital divide persist. The article concludes by emphasizing the need for inclusive policies and international collaboration to harness the full potential of the creative economy
Keywords: Creative economy; sustainable development; innovation; cultural preservation